The Influence of Hedonic Shopping Value and Allowance on Impulse Buying of Shopee Products among Accounting Education Students at UMS Class of 2017 - Aningsih, Adella Yovie (Universitas Muhammadiyah Surakarta, 2024)
The aim of this research is to determine: the influence of hedonic shopping and pocket money on impulse buying that occurs among UMS Accounting Education students class of 2017. This research includes quantitative research and hypothesis testing. The population in this study were students majoring in Accounting, Class of 2017, Muhammadiyah University of Surakarta, totaling 243 students and the sample used was 96 students. In this research, we will use a snowball sampling technique, where samples are taken based on previous sample searches. The data analysis techniques used in this research are Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Analysis Test, T Test, F Test, and Coefficient of Determination. The results of this research state that: 1) Based on the results of hypothesis testing by calculating data results, hedoning shopping value does not have a positive and significant effect on impulse buying of Shopee products. With results showing a positive β1 coefficient value of 0.027, the t-count value is 0.237 with a significant value of 0.813 so the first hypothesis is rejected. This explains that hedonic shopping value has no effect on impulse buying of Shopee products. 2) Based on the results of hypothesis testing by calculating the data results, money does not have a positive and significant effect on impulse buying of Shopee products. With results showing a positive β2 coefficient value of 0.231, the t-count value is 1.349 with a significant value of 0.180 so the second hypothesis is rejected. This explains that pocket money has no effect on impulse buying of Shopee products.